Education and socioeconomic status as predictors of refugee mental health: insights from a study of Jordan-based Syrian refugee sample - Atrooz, Fatin; Khabour, Omar F.; Almomani, Fidaa; Aljararwah, Sally; Alfurjani, Batool H.; Salim, Samina (Frontiers in Public Health, 2024)
Background-The Syrian civil war is considered as the greatest humanitarian crisis in modern history, which has resulted in a major refugee crisis. A significant concern is the high prevalence of mental disorders such as depression, anxiety, and post-traumatic stress disorder (PTSD) among Syrian refugees. While the focus of most refugee mental health research has been pre-migration trauma, post-migration challenges and stressors, which can also be significant determinants of mental health, are often ignored. The purpose of this study was to assess mental health of Syrian refugees as compared to local Jordanians, and to examine sociodemoghraphic factors and perceived stressors that are associated with mental distress among participants. Methods-This was a cross sectional study conducted in northern region of Jordan among Syrian refugee and Jordanian adults. We used the validated Arabic version of Afghan Symptoms Checklist (ASC) to assess mental distress among participants. Results-A total of 929 subjects (43% Syrian refugees, 56% females) participated in this study. Disparities in education, monthly income, and health insurance were significant between Syrian refugees and Jordanians, p<0.001. The mean score in ASC was significantly higher among Syrian refugees, particularly among refugee females (mean ASC score±standard deviation: Syrian refugee females: 58.22±1.13; Syrian refugee males: 45.31±1.28; Jordanian females: 51.06±0.91; Jordanian males: 46.45±1.08, p=0.002). Multivariable linear regression showed that the estimated difference in the mean of ASC score between males and females is 7.42 (p<0.001), and the estimated mean difference between Syrian refugees and Jordanians is 2.76 (p=0.019). Interestingly, the estimated mean of ASC scores for individuals with high education level is decreased by 4.18 as compared to individuals with lower education level (high school or less), p<0.001. Conclusions-Education level was highly predictable of mental distress of Syrian refugees, particulary female refugees. Enhancing higher educational opportunities is proposed for improving socioeconomic status of refugees which might serve as a buffering strategy for mental distress among this vulnerable population.